Effects of Microplastics on Fish and in Human Health - Bhuyan, Md. Simul (Frontiers in Environmental Science, 2022)
Microplastics (MPs) are regarded as a global issue due to their toxicity effects on fish and humans. Fish is a vital origin of human protein, which is necessary for body growth. Contamination of fish by MPs is a major hazard that requires special focus. After exposure to MPs alone or in combination with other pollutants, fish may experience a variety of health issues. MPs can cause tissue damage, oxidative stress, and changes in immune-related gene expression as well as antioxidant status in fish. After being exposed to MPs, fish suffer from neurotoxicity, growth retardation, and behavioral abnormalities. The consequences of MPs on human health are poorly understood. Due to the abundance of MPs in the environment, exposure may occur via consumption, inhalation, and skin contact. Humans may experience oxidative stress, cytotoxicity, neurotoxicity, immune system disruption, and transfer of MPs to other tissues after being exposed to them. The toxic effects of MPs in both fish and human are still unknown. This detailed review has the potential to add to existing knowledge about the ecotoxicity effects of MPs in both fish and humans, which will be useful for the forthcoming study.